Contrast in Matthew Arnold’s The Scholar Gipsy and Kahlil Gibran’s Al-Mawakib: A Contrastive Stylistic Analysis (Journal of the College of Languages (JCL), 2024)
Poetry is regarded an interesting area of inquiry in linguistic studies due to its eccentric and aesthetic use of language. A lot of studies have been carried out so far for the analysis of poetry, yet few have dealt with pastoral poetry. The present research attempts to investigate the language of pastoral poetry in two different languages i.e. English and Arabic with the aim of finding similarities and differences. The data of the study consists of one English and one Arabic pastoral poems. Leech and Short's (2007) checklist is used as a model for analysis. The findings of the study reveal that there are more similarities than differences between English and Arabic pastoral poems as the poems rely on contrast in the use of the lexical categories with differences in the distribution of these categories only.